The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.2478/picbe-2019-0088
|View full text |Cite
|
Sign up to set email alerts
|

Alleviating energy poverty experienced by students living in private rented accommodation: The role of the housing provider

Abstract: Students are often described as an under-reported and under-supported group of the population falling into energy poverty. Although the main drivers of energy poverty are well documented, up to this date little attention is given to housing tenure as a cause of energy poverty. This study aims to support the understanding of the motivations and barriers faced by property owners that rent accommodation to students for making energy efficiency improvements to their rented properties. With this understanding recom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…The actions heading towards providing better insulation for buildings rented to students will be beneficial for the process of curtailing the energy poverty of students. The studies conducted among the landlords renting apartments to students in seven EU countries showed that grants and financial incentives are pivotal in convincing landlords to make investments in this area [58].…”
Section: Discussionmentioning
confidence: 99%
“…The actions heading towards providing better insulation for buildings rented to students will be beneficial for the process of curtailing the energy poverty of students. The studies conducted among the landlords renting apartments to students in seven EU countries showed that grants and financial incentives are pivotal in convincing landlords to make investments in this area [58].…”
Section: Discussionmentioning
confidence: 99%
“…Our findings closely align with the existing international literature. European [22,23] and Japanese studies [24] have shown that tertiary students are at greater risk compared to the general population, with poor housing conditions, particularly in the private rental sector, driving this difference [19,22]. Internationally there is a recognised need for regulation to encourage energy efficiency improvements in the private rental sector [16,25,26]; our study shows that better regulation is needed in New Zealand too.…”
Section: Tertiary Students' Experience Of Energy Povertymentioning
confidence: 62%
“…Studies exploring energy poverty among tertiary student population groups in England [19][20][21], Europe [22,23], and Japan [24] have confirmed that tertiary students are at greater risk compared to the general population. Poor housing conditions, particularly in the private rental sector, contribute to adverse mental and health outcomes among tertiary students [19,22].…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, the phenomenon of energy poverty is observed either in the form of insufficient access to energy services for developing countries or in the form of excessive energy costs in relation to the disposable income of households in developed countries (Nussbaumer et al, 2012). Although the main drivers of energy poverty are well documented, up to this date little attention has been given to students as a vulnerable group affected by energy poverty (Kousis et al, 2020); student energy poverty is often under-reported and under-supported (Ntouros et al, 2019). Thus, the adoption of environmentally conscious behaviour among university students as a result of informative campaigns, coupled with educational programs aiming to promote energy saving lifestyles and environmental consciousness to students, contributes significantly to energy saving, alleviates exposure to energy poverty and paves the way for decarbonization (Tsagarakis et al, 2011).…”
Section: Problem Statementmentioning
confidence: 99%